THE EFFECT OF ACCOUNTABILITY, TRANSPARENCY OF FINANCIAL REPORTING AND QUALITY OF ACCOUNTING INFORMATION ON THE LEVEL OF RECEIVING ZAKAT FUNDS WITH ACCESTABILITY AS A MODERATION VARIABLE AT BAZNAS IN BATAM CITY - Afrinanda; Chabullah Wibisono; Robin; Bambang Satriawan; Muammar Khaddafi (RADJA PUBLIKA, 2023)
This study aims to analyze and provide empirical evidence about the effect of accountability, transparency of financial reporting and quality of accounting information on the level of acceptance of zakat funds with accessibility as a moderating variable. The population of this research is the muzakki who pay their zakat directly to BAZNAS Batam City. The sampling technique in this study used random sampling. This study used the slovin formula with an error rate of 1% so that a total of 96 samples were obtained. This study uses primary data with a quantitative approach. The primary data collection method is through a questionnaire which is measured using a Likert scale. The data analysis method uses Partial Least Square (PLS) with the SmartPLS application. The test results show that accountability has a significant effect on the level of acceptance of zakat with a P-Value of 0.000 <0.05, transparency has an insignificant positive effect on the level of acceptance of zakat with a P-Value of 0.172 <0.05, and the quality of accounting information has a significant effect on financial supervision with a P-Value of 0.000 <0.05 but accessibility has no significant negative effect on the level of zakat acceptance. Meanwhile, accessibility does not moderate the relationship between accountability, transparency and quality of accounting information on the level of zakat acceptance. This moderating effect is called predictor moderation. Transparency has a not significant positive effect on the level of zakat acceptance with a P-Value of 0.172 <0.05, and the quality of accounting information has a significant effect on financial supervision with a P-Value of 0.000 <0.05 however accessibility has an insignificant negative effect on the level of zakat acceptance . Meanwhile, accessibility does not moderate the relationship between accountability, transparency and quality of accounting information on the level of zakat acceptance. This moderating effect is called predictor moderation. Transparency has a not significant positive effect on the level of zakat acceptance with a P-Value of 0.172 <0.05, and the quality of accounting information has a significant effect on financial supervision with a P-Value of 0.000 <0.05 however accessibility has an insignificant negative effect on the level of zakat acceptance . Meanwhile, accessibility does not moderate the relationship between accountability, transparency and quality of accounting information on the level of zakat acceptance. This moderating effect is called predictor moderation. accessibility does not moderate the relationship between accountability, transparency and quality of accounting information on the level of zakat acceptance. This moderating effect is called predictor moderation. accessibility does not moderate the relationship between accountability, transparency and quality of accounting information on the level of zakat acceptance. This moderating effect is called predictor moderation.